Frank Julian Sprague : Electrical Inventor and Engineer - Middleton, William D., 1928-2011; Middleton, William D., 1961- (Book collections on Project MUSE., 2009)
Frank Julian Sprague invented a system for distributing electricity to streetcars from overhead wires. Within a year, electric streetcars had begun to replace horsecars, sparking a revolution in urban transportation. Sprague (1857-1934) was an American naval officer turned inventor who worked briefly for Thomas Edison before striking out on his own. Sprague contributed to the development of the electric motor, electric railways, and electric elevators. His innovations would help transform the urban space of the 20th century, enabling cities to grow larger and skyscrapers taller. The Middletons' generously illustrated biography is an engrossing study of the life and times of a maverick innovator.